BAP1 shapes the bone marrow niche for lymphopoiesis by fine-tuning epigenetic profiles in endosteal mesenchymal stromal cells - Jeong, Jinguk; Jung, Inkyung; Kim, Ji-Hoon; Jeon, Shin; Hyeon, Do Young; Min, Hyungyu; Kang, Byeonggeun; Nah, Jinwoo; Hwang, Daehee; Um, Soo-Jong; Ko, Myunggon; Seong, Rho Hyun (Nature Publishing Group, 2022)
Hematopoiesis occurs within a unique bone marrow (BM) microenvironment, which consists of various niche cells, cytokines, growth factors, and extracellular matrix components. These multiple components directly or indirectly regulate the maintenance and differentiation of hematopoietic stem cells (HSCs). Here we report that BAP1 in BM mesenchymal stromal cells (MSCs) is critical for the maintenance of HSCs and B lymphopoiesis. Mice lacking BAP1 in MSCs show aberrant differentiation of hematopoietic stem and progenitor cells, impaired B lymphoid differentiation, and expansion of myeloid lineages. Mechanistically, BAP1 loss in distinct endosteal MSCs, expressing PRX1 but not LEPR, leads to aberrant expression of genes affiliated with BM niche functions. BAP1 deficiency leads to a reduced expression of pro-hematopoietic factors such as Scf caused by increased H2AK119-ub1 and H3K27-me3 levels on the promoter region of these genes. On the other hand, the expression of myelopoiesis stimulating factors including Csf3 was increased by enriched H3K4-me3 and H3K27-ac levels on their promoter, causing myeloid skewing. Notably, loss of BAP1 substantially blocks B lymphopoiesis and skews the differentiation of hematopoietic precursors toward myeloid lineages in vitro, which is reversed by G-CSF neutralization. Thus, our study uncovers a key role for BAP1 expressed in endosteal MSCs in controlling normal hematopoiesis in mice by modulating expression of various niche factors governing lymphopoiesis and myelopoiesis via histone modifications.